(untitled) (Gestão & Regionalidade, 2024)
This study aims to analyze the relationship between the administrative agenda disseminated in the Brazilian public sector by innovation laboratories and the main characteristics of the bureaucratic organization The research was classified as an exploratory study and its analysis followed the techniques of content analysis, carried out with the aid of the Iramuteq software. As a result, it was identified (a) that laboratories are safe spaces for testing and help to propagate the culture of innovation, (b) that leadership is important to ensure the execution of ideas and projects, (c) that it is difficult to measure results and select demands and (d) that the practice of innovation laboratories express the departure from bureaucratic logic